PENGARUH PEMBERIAN JERAMI DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI (Oryza sativa L) - Meiyana Hikmawati (Universitas Panca Marga Probolinggo, 2019)
The objectives of this research is the effect of straw and range on the yield of rice (Oryza sativa L). The method of the research use factorial design based on the Randomized Block Design with two factors of treatment. The first factor was straw (without straw (P0), fermented straw (P1) dan straw burned (P2)) and second factor was range (spacing of 25 x 20 cm (J1), spacing of 25 x 25 cm (J2) and spacing of 25 x 30 cm (J3)) and each kombination of treatment three times replicated so that it is obtained 9 trial combinations and 27 trial plots. The result of the research : (1) There was not interaction between straw and range on the yield of rice (Oryza nivara). (2) The highest yield was treatment P1(fermented straw) for all parameters except plant height in 14 hst, penicle length per clump and weight of 1000 grains of dry grains milled. (3) The highest yield was treatment J3 (spacing of 25 x 30 cm) for all parameters except weight of grain per plot dan weight of 1000 grains of dry grains milled. Key word : straw, range and interaction.